New Coupled-Particle Light-Scattering Assay for Detection of Ro/SSA (52 and 60 Kilodaltons) and La/SSB Autoantibodies in Connective Tissue Diseases - Bizzaro, Nicola; Bonelli, Fabrizio; Tonutti, Elio; Tozzoli, Renato; Villalta, Danilo (Clinical and Diagnostic Laboratory Immunology, 2001)
Classifications Services CVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CVI About CVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1556-6811 Online ISSN: 1556-679X Copyright © 2014 by the American Society for Microbiology. For an alternate route to CVI .asm.org, visit: CVI